2022
DOI: 10.1039/d2cc02888c
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced synthesis of fluorescent hydrogels without fluorescent monomers

Abstract: A fluorescent monomer-free one-step strategy is developed for the synthesis of fluorescent acrylamide gels, using inexpensive and commercially available rhodamine B as the hydrogen donor in type II photoinitiation system....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, the expensive price, lack of eco-friendliness, and incompatibility with hydrogel matrix of fluorescent monomers limit the further development of fluorescent smart hydrogels in this field. , Recently, carbon dots (CDs) has been widely known as a promising luminescent nanomaterial with abundant low-cost sources, facile synthetic methods, excellent biocompatibility, high chemical stability, significant water solubility, low cytotoxicity, and excellent optoelectronic properties, attracting great attention in many fields including biomedicine, catalysis, optoelectronic devices, and especially anticounterfeiting. Many scholars demonstrated that integrating CDs into desirable polymer matrix is a cost-effective and environmentally friendly method to develop flexible materials for information encryption. For instance, Xiong et al reported a flexible right-hand chiral fluorescent film with potential applications in sensing and anti-counterfeiting .…”
Section: Introductionmentioning
confidence: 99%
“…However, the expensive price, lack of eco-friendliness, and incompatibility with hydrogel matrix of fluorescent monomers limit the further development of fluorescent smart hydrogels in this field. , Recently, carbon dots (CDs) has been widely known as a promising luminescent nanomaterial with abundant low-cost sources, facile synthetic methods, excellent biocompatibility, high chemical stability, significant water solubility, low cytotoxicity, and excellent optoelectronic properties, attracting great attention in many fields including biomedicine, catalysis, optoelectronic devices, and especially anticounterfeiting. Many scholars demonstrated that integrating CDs into desirable polymer matrix is a cost-effective and environmentally friendly method to develop flexible materials for information encryption. For instance, Xiong et al reported a flexible right-hand chiral fluorescent film with potential applications in sensing and anti-counterfeiting .…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar methodology, more recently, we reported fluorescent hydrogel synthesis without fluorescent monomers for the first time, using rhodamine B (RhB) and benzophenone (BP) as bimolecular photoinitiation system. [11] Both reactions operate at room temperature and they benefit from the inherent characteristics of photopolymerization, in that the temporal and spatial control can be achieved by simply switching on and off the light source. [12] Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the copolymerisation of AaM, BIS, and Aac adsorbed onto the nanoparticles, is expected to occur through the radical generation on the tertiary amine moiety of the RhB. Previously, we have shown that RhB-incorporated acrylamidebased hydrogels showed limited or no leakage over time, 21 suggesting that the fluorescent moieties were incorporated covalently into the polymer network; therefore, the reaction is likely to proceed in the proposed pathway, where RhB acts as a coinitiator in the presence of BP.…”
mentioning
confidence: 98%
“…Following the first report on type II photoinitiated precipitation polymerisation for microsphere functionalisation, 20 we recently reported the use of a bimolecular photoinitiator system to synthesise fluorescent polyacrylamide nanoparticles in one step using rhodamine B (RhB) and benzophenone (BP), as a hydrogen donor and photosensitiser, respectively. 21 The synthesised polymeric nanoparticles were fluorescent, stable and easy to produce and the size of the nanomaterials could be adjusted by changing the monomer concentration in the feed. As a continuation of our efforts to find more effective and cost-efficient methods for in situ synthesis and functionalisation of polymers, more recently, we applied this strategy for the synthesis of highly cross-linked and fluorescent polymer microspheres by precipitation polymerisation.…”
mentioning
confidence: 99%